Experiencing Grace: A Review of the Empirical Literature. Issue 3 (4th May 2022) - Hodge, Adam S.; Hook, Joshua N.; Davis, Don E.; Van Tongeren, Daryl R.; Bufford, Rodger K.; Bassett, Rodney L.; McMinn, Mark R.
ABSTRACT: Positive psychologists have used science to understand many virtues but have only just started to study grace, recently defined as ' … the gift of acceptance given unconditionally and voluntarily to an undeserving person by an unobligated giver'. The purpose of the current article is to provide a systematic review of all empirical studies (published and unpublished) on grace. Broadly, the empirical study of grace has focused on what people believe and how people experience both divine and human grace. Additionally, empirical attention has shifted to explore outcomes of grace-based interventions (e.g., congregation-wide interventions, marital interventions). In general, beliefs and experiences of grace were associated with (a) positive mental health outcomes, (b) religiosity, (c) virtue development, and (d) interpersonal functioning. Human grace has not been extensively explored and divine grace has been studied mostly among Christians; future studies should address these limitations and explore causal relationships.